2008
DOI: 10.1093/brain/awn240
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to aquaporin-4 in the long-term course of neuromyelitis optica

Abstract: Neuromyelitis optica (NMO) is a severe inflammatory CNS disorder of putative autoimmune aetiology, which predominantly affects the spinal cord and optic nerves. Recently, a highly specific serum reactivity to CNS microvessels, subpia and Virchow–Robin spaces was described in patients with NMO [called NMO–IgG (NMO–immunoglobulin G)]. Subsequently, aquaporin-4 (AQP4), the most abundant water channel in the CNS, was identified as its target antigen. Strong support for a pathogenic role of the antibody would come … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
342
4
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(376 citation statements)
references
References 20 publications
15
342
4
15
Order By: Relevance
“…The presence of NMO-IgG is specific for NMO, and in some reports serum NMO-IgG titers correlate with NMO disease activity (2,3). Studies in rodents suggest that NMO-IgG is pathogenic in NMO.…”
mentioning
confidence: 99%
“…The presence of NMO-IgG is specific for NMO, and in some reports serum NMO-IgG titers correlate with NMO disease activity (2,3). Studies in rodents suggest that NMO-IgG is pathogenic in NMO.…”
mentioning
confidence: 99%
“…In line with these findings AQP4-IgG transiently increase after initiation of rituximab, with a subsequent decrease [107]. Lower titers of AQP4-IgG are probably associated with less disease activity but have not yet been established as a reliable biomarker of treatment response in rituximab-treated patients [74,100,101]. It is unknown whether the clinical effects of B-cell depletion are mediated by a reduction of AQP4-IgG or by inhibition of other proinflammatory B-cell functions.…”
Section: Rituximab and Other B-cell-depleting Therapiesmentioning
confidence: 92%
“…Several studies including a total of almost 400 patients have shown that AZA reduces the ARR, sometimes associated with improvement of neurological disability [17,[74][75][76][77][78][79][80]. A retrospective study evaluating classical NMO and patients with AQP4-IgG-positive NMOSD reported a decrease in the mean ARR from 2.18 to 0.64 in 70 patients treated with AZA for >1 year, with or without concomitant corticosteroid therapy [77].…”
Section: Azamentioning
confidence: 99%
“…NMO-IgG detection is a strong predictor of recurrence after an initial spinal or optic attack (Jarius et al, 2008(Jarius et al, , 2010b. In few patients, NMO-IgG was high during flares and became negative during the stabilized disease following treatment, and in contrary, an initially seronegative patient became positive during a further attack (Weinstock-Guttman et al, 2008).…”
Section: Nmo-igg and Complement As Key Factorsmentioning
confidence: 99%